International Trade Spillovers from Domestic COVID-19 Lockdowns - Aiyar, Shekhar (IMF Working Papers; Working Paper ;, 2022)
While standard demand factors perform well in predicting historical trade patterns, they fail conspicuously in 2020, when pandemic-specific factors played a key role above and beyond demand. Prediction errors from a multilateral import demand model in 2020 vary systematically with the health preparedness of trade partners, suggesting that pandemic-response policies have international spillovers. Bilateral product-level data covering about 95 percent of global goods trade reveals sizable negative international spillovers to trade from supply disruptions due to domestic lockdowns. These international spillovers accounted for up to 60 percent of the observed decline in trade in the early phase of the pandemic, but their effect was shortlived, concentrated among goods produced in key global value chains, and mitigated by the availability of remote working and the size of the fiscal response to the pandemic.